Political fragmentation and government spending : bringing ideological polarization into the picture (2010)
Governments adopt projects targeted to the constituencies of legislators either because legislators have direct participation in the design of the budget, or because they demand those projects in exchange for support to the government's initiatives in Congress. We study empirically the idea that, when the second channel predominates, the effect of party fragmentation on government spending (well established in the literature) is positive only in environments with high ideological polarization. The reason is that it is precisely in polarized environments where the government faces greater difficulties in getting its initiatives approved. We take this hypothesis to data for a set of presidential democracies, where we expect the use of spending in exchange for support to be most predominant. We find that party fragmentation has no effect on government spending in the absence of ideological polarization, and a positive effect when polarization is high enough. Implementing the same set of exercises for parliamentary democracies, we find that the effect of fragmentation in this case is not intermediated by the degree of polarization...